2019
DOI: 10.1177/2050640619826847
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of apelin preconditioning in a rat model of hepatic ischemia reperfusion injury; possible interaction between the apelin/APJ system, Ang II/AT1R system and eNOS

Abstract: Introduction: Hepatic ischemic reperfusion injury occurs in multiple clinical settings. Novel potential protective agents are still needed to attenuate this injury. Apelin preconditioning protects against ischemic reperfusion injury in different organs. However, the protective mechanism of apelin on hepatic ischemic reperfusion injury is not yet clear. Aim: Evaluate the effect of apelin-13 preconditioning on hepatic ischemic reperfusion injury and clarify possible interactions between apelinergic, renin-angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…The activated PI3K/ Akt signaling pathway promotes the generation of heme oxygenase-1 (HO-1) by upregulating the expression of Nrf2, thus alleviating oxidative stress injury during LIRI (43)(44)(45)(46)(47). In addition, activation of PI3K/Akt pathway can activate endothelial nitric oxide synthase (eNOS) in vascular endothelial cells, increase the formation of nitric oxide (NO), and further improve LIRI (48)(49)(50).…”
Section: Pi3k/akt Signaling Pathway and Oxidative Stressmentioning
confidence: 99%
“…The activated PI3K/ Akt signaling pathway promotes the generation of heme oxygenase-1 (HO-1) by upregulating the expression of Nrf2, thus alleviating oxidative stress injury during LIRI (43)(44)(45)(46)(47). In addition, activation of PI3K/Akt pathway can activate endothelial nitric oxide synthase (eNOS) in vascular endothelial cells, increase the formation of nitric oxide (NO), and further improve LIRI (48)(49)(50).…”
Section: Pi3k/akt Signaling Pathway and Oxidative Stressmentioning
confidence: 99%
“…Data reported in literature reveal that apelinergic signaling plays a crucial role in decreased ROS production [101] and protection the heart against ischemia/reperfusion injury activating Akt, ERK/MAPK, and eNOS pathways [102,103].…”
Section: Apelin/apj Axis: Biological Rolementioning
confidence: 99%
“…Studies have shown that apelin-13 is able to penetrate the blood-brain barrier via an unsaturated mechanism, which indicates that it is feasible to transport to the central nervous system pharmacologically through peripheral pathways [33]. Apelin-13 is a neuropeptide which is capable of protecting against neuronal apoptosis and excitotoxicity in vitro, and is associated with neuronal survival in vivo following cerebral ischemia or ischemia/reperfusion injury, amyotrophic lateral sclerosis (ALS), and seizure [34][35][36]. In addition, apelin-13 has an attenuating effect on the expression of pro-inflammatory cytokines, and inhibits microglia, astrocytes, and other inflammatory cells [37,38].…”
Section: Discussionmentioning
confidence: 99%